2018
DOI: 10.37077/25200860.2018.74
|View full text |Cite
|
Sign up to set email alerts
|

Growth parameters of common carp Cyprinus carpio cultivated in semi- closed system

Abstract: Growth parameters of common carp Cyprinus carpio were investigated in 13 plastic tanks (550 cm diameter and 130 cm depth) of semi-closed system at Abu Al- Khaseeb District, Basrah from 27 October to 17 December, 2016. Number of fishes in every tank was 1300 with an average initial weight 101.9 g. Fishes were fed at a ratio of 5% on sinking pelleted food manufactured in Basrah University factory with 25% protein ratio. Results of current study exhibited highest final weight (381.1 g) achieved by fishes reared i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Mirror carp (C. carpio) recorded SGR of 4.95 and 4.80 %day-1 in two densities during 90 days (Hossain et al, 2014). Taher et al (2018) revealed SGR of 2.44 %/day and FCR of 2.12 for common carp reared in semi-closed system for 52 days. Taher (2020) recorded WI of 484.5-411.4, DGR of 4.07-8.21 g/day and FCR of 2.56-7.07 when investigated four imported floating pellets.…”
Section: Discussionmentioning
confidence: 94%
“…Mirror carp (C. carpio) recorded SGR of 4.95 and 4.80 %day-1 in two densities during 90 days (Hossain et al, 2014). Taher et al (2018) revealed SGR of 2.44 %/day and FCR of 2.12 for common carp reared in semi-closed system for 52 days. Taher (2020) recorded WI of 484.5-411.4, DGR of 4.07-8.21 g/day and FCR of 2.56-7.07 when investigated four imported floating pellets.…”
Section: Discussionmentioning
confidence: 94%
“…Enache et al (2011) recorded 1.07 %day -1 as specific growth rate and 1.49 as feed conversion rate of common carp cultivated in RAS for 30 days. Common carp showed specific growth rate of 2.44 %day -1 and feed conversion rate of 2.12 when reared in semi-closed system for 52 days (Taher et al, 2018). Coroian et al (2015) stated that life food had positive effects for growth of common carp fingerlings comparing with traditional feeds.…”
Section: Resultsmentioning
confidence: 99%
“…Mirror carp (C. carpio) recorded SGR of 4.95 and 4.80 % day -1 in two densities during 90 days (Hossain et al, 2014). Taher et al (2018) pointed out that SGR of 2.44 % day −1 and FCR of 2.12 for common carp reared in semi-closed system for 52 days. Taher (2020) recorded DGR of 4.07-8.21 g day −1 , FCR of 2.56-7.07 when investigated four imported floating pellets.…”
Section: Discussionmentioning
confidence: 97%